2012
DOI: 10.1111/j.1467-8551.2011.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of New Product Development's Front‐end Knowledge Conceptualization Process in Discontinuous Innovations

Abstract: Organizational knowledge creation, as reflected in new product/service development, is a vital process for firms to master. Critical to the development of new products/services is the management of the front-end phase, which crucially determines the eventual fate of a new product/service idea. However, studies on how knowledge is created at the front-end of the new product development process are rare. This empirical paper addresses this gap by focusing on knowledge conceptualization - where new knowledge from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 104 publications
(133 reference statements)
0
25
0
Order By: Relevance
“…Our model shows that the frequency, characteristics and types of loops are not uniform across the front-end. In line with the varying frequency of social interactions (Akbar and Tzokas, 2013), loops gradually increase from the generation-evaluation interface to maximize at the expansion-refinement interface, and decrease at the crystallization stage. In addition, loops diverge and magnify along the expansion-refinement interface, and converge thereafter.…”
Section: Discussionmentioning
confidence: 92%
“…Our model shows that the frequency, characteristics and types of loops are not uniform across the front-end. In line with the varying frequency of social interactions (Akbar and Tzokas, 2013), loops gradually increase from the generation-evaluation interface to maximize at the expansion-refinement interface, and decrease at the crystallization stage. In addition, loops diverge and magnify along the expansion-refinement interface, and converge thereafter.…”
Section: Discussionmentioning
confidence: 92%
“…Using different technologies and methods can increase the speed of problem solving, prototyping and continuous testing (Saff & Ernst, 2003), or improve the FFE by using information systems and knowledge sharing (Gordon et al, 2008) or knowledge management (Akbar & Tzokas, 2013).…”
Section: Improved Analysis and Information Processing And Intuitionmentioning
confidence: 99%
“…According to some authors, intelligent planning and the reduction of technical and market uncertainty explain later success (Verworn, Herstatt & Nagahira, 2008) for example by using tools to help innovators track and assess front-end fuzziness from different sources (Chang, Chen & Wey, 2007) and having engaged management attention to reduce uncertainty (Poskela & Martinsuo, 2009). Uncertainty affects the FFE, therefore early involvement of all departments, planning prior to development, and reducing market and technical uncertainty positively affect product development success (Akbar & Tzokas, 2013). A contingency argument has been presented; as uncertainty reduction seems to be a viable strategy, especially for incremental innovation, improved analysis and preparation can facilitate a better outcome (Verworn, Herstatt & Nagahira, 2008).…”
Section: Uncertainty Reductionmentioning
confidence: 99%
“…Prior research on managing NPD has shown that the front end of NPD often has a dynamic and interactive nature (Akbar and Tzokas 2013). This stage is characterized by complex information processing (Khurana and Rosenthal 1997;De Brentani and Reid 2012), ad hoc decision-making (Montoya-Weiss and O'Driscoll 2000), and conflicting organizational pressures caused by, for example, high degrees of complexity and uncertainty (Chang et al 2007).…”
Section: Introductionmentioning
confidence: 99%